Thymoquinone, an active ingredient of Black Seed (Nigela saliva) induces distinct apoptotic pathways in C33A and Siha Cervical Cancer Cell Lines) - Ichwan, Solachuddin JA; Al-Ani, Imad Matloub Dally; Suriyah, Wastuti; Muhammad, Taher (2012)
Thymoquinone (TQ) is the main constituent of black seed (Nigella sativa, spp) essential oil, which shows promising in vitro and in vivo anti-neoplastic activities against different tumor cell lines. However, the apoptotic effects of TQ and how TQ induces apoptosis in cervical cancer cells still remains to be clarified. Cervical cancers have been generally treated by combination of surgery and/or chemo-radiotherapy. However that is not applicable to a later stage of the cancer whereby only palliative treatment is available with many side effects. p53 gene is a specific gene that functions to suppress the growth of tumors. The gene is frequently lost or inactivated in cervical cancers. This research was aimed to explore the apoptotic mechanism of TQ in inducing apoptosis on two different human cervical cell lines; Siha and C33A cells. The cell lines harbor distinct non-functional p53 tumor suppressor gene. Although p53 is wild-type in Siha, the cells expressing E6 oncoprotein that diminishing the endogenous p53 function, whereas in C33A cells, the p53 is mutated. We found that TQ stimulates distinct apoptotic pathway in Siha and C33A cells. TQ markedly induced apoptosis as demonstrated by DNA fragmentation assay in both cell lines. Moreover, we demonstrated for the first time that TQ-induced apoptosis in Siha cells through p53-dependent pathway as shown by elevated level of p53-mediated apoptosis target genes as shown by Quantitative PCR analysis, whereas in C33A cells is mainly associated with the activation of Caspase-3. These results support further research in exploring the potential clinical usefulness of TQ for cervical cancers treatment.